2019
DOI: 10.21608/edj.2019.72618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zirconia Nanoparticles Incorporation on Some Properties of One High - Impact Heat cured PMMA Resin

Abstract: PURPOSE: To evaluate the effect of ZrO 2 nanoparticles incorporation (in two different ratios 1% and 3%) on some properties of one high-impact heat cured PMMA resin material when it was processed by two different methods (Conventional and Microwave curing methods). Materials & Methods: One high-impact heat cured PMMA resin (Trevalon Hi) was used in this study to be modified with nano-ZrO 2 in two different ratios (1% and 3%). Both unmodified and modified high-impact heat cured PMMA resin were subjected to thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…This result comes in agreement with Ihab et al [9] who compared the color differences after ZNP addition and showed a significant difference between control and modified specimens and reported that ΔEab was increased with the increasing of ZNP concentration. On the other hand, this finding is in disagreement with previous studies [27,46]. The discrepancies between the results of this study and other articles may be explained by the differences in experimental methodology, concentrations of tested NPs as well as the usage of different types of PMMA material.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result comes in agreement with Ihab et al [9] who compared the color differences after ZNP addition and showed a significant difference between control and modified specimens and reported that ΔEab was increased with the increasing of ZNP concentration. On the other hand, this finding is in disagreement with previous studies [27,46]. The discrepancies between the results of this study and other articles may be explained by the differences in experimental methodology, concentrations of tested NPs as well as the usage of different types of PMMA material.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, previous studies agreed with the present findings and reported that PMMA color was changed to pale pinkish white with ZNP addition [43,44] and as the concentration of ZNP increased, the color change was increased [24,45]. On the other hand, our findings are in disagreement with other studies which concluded that the addition of ZNP displayed insignificant color changes of PMMA [27,46].…”
Section: Discussionsupporting
confidence: 68%
“…(2) Various methods have been used to improve the strength of PMMA including giving more bulkiness to the material in the susceptible areas, co-polymerization, cross-linking, (3,4) and the addition of different reinforcing fibers. (5) Recently, many studies have investigated the reinforcement of PMMA denture base materials through incorporating different types and concentrations of nanoparticles such as Silicon Dioxide (SiO 2 ) , (6,7,8) Titanium Dioxide (TiO 2 ) , (8,9,10) Silver (Ag), (10,11,12) Aluminium Oxide (AL 2 O 3 ), (12,13) Zirconium Dioxide (ZrO 2 ), (14,15) Zinc oxide (ZnO), (16) and Copper Oxide (CuO). (17) According to these studies, the properties of the reinforced material depend mainly on the size and concentration of the used nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors tried to reinforce the PMMA acrylic resins with metal oxide nanoparticles. Nanotechnology recently introduces a new era for reinforcing materials; because of nanomaterials' physical, chemical, mechanical, and biological properties ( Elhatery, 2019 , Gad and Abualsaud, 2019 a , Vikram and Chander, 2020 ). Nowadays, zirconium oxide (ZrO 2 ) nanoparticles have been applied as a reinforcing agent owing to their biocompatibility, advantageous mechanical properties as well as antifungal properties of ZrO 2 ( Alhavaz et al, 2017 , Akay and Avukat, 2019 ).…”
Section: Introductionmentioning
confidence: 99%